Variable Response of Norepinephrine Transporter to Traumatic Stress and Relationship to Hyperarousal - Nwokafor, Chiso; Serova, Lidia I.; Tanelian, Arax; Nahvi, Roxanna J.; Sabban, Esther L. (Frontiers in Behavioral Neuroscience, 2021)
The noradrenergic systems play a key role in stress triggered disorders such as post-traumatic stress disorder (PTSD). We hypothesized that traumatic stress will alter expression of norepinephrine transporter (NET) in locus coeruleus (LC) and its target brain regions which could be related to hyperarousal. Male Sprague-Dawley rats were subjected to single prolonged stress (SPS) and several weeks later the LC was isolated. NET mRNA levels in LC, determined by RT-PCR, displayed variable response with high and low responsive subgroups. In different cohort, acoustic startle response (ASR) was measured 2 weeks after SPS and levels of NET mRNA and protein in LC determined. The high NET responsive subgroup had greater hyperarousal. Nevertheless, NET protein levels, as determined by western blots, were lower than unstressed controls in LC, ventral hippocampus and medial prefrontal cortex and displayed considerable variability. Hypermethylation of specific CpG region in promoter of SLC6A2 gene, encoding NET, was present in the low, but not high, NET mRNA responsive subgroup. Taken together, the results demonstrate variability in stress elicited changes in NET gene expression and involvement of epigenetic changes. This may underlie mechanisms of susceptibility and resilience to traumatic stress triggered neuropsychiatric symptoms, especially hyperarousal.